2012
DOI: 10.5861/ijrsll.2012.168
|View full text |Cite
|
Sign up to set email alerts
|

The effects of simultaneous use of pre-planning along +/-Here-and-Now dimension on fluency, complexity, and accuracy of Iranian EFL learners’ written performance

Abstract: Nowadays, plethora of research on pre-task planning has attempted to find out the effect of planning time on oral production of L2 learners. By and large, it has been reported planning has had a positive impact on their task-performance. Nonetheless, there have been few bodies of research performed with regard to planning in writing contexts, and there has been no conclusive evidence to illustrate the fact that pre-task planning enhances L2 learners' written performance in the ways which lots of researchers ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
3
1
Order By: Relevance
“…The result of that study is in line with ours in terms of lexical complexity, but accuracy was not measured in their study. Similar to that study, Mohammadzadeh Mohammadabadi et al (2013) also did not find any interaction effect between planning time and here-and-now dimensions of task complexity. Additionally, Ong and Zhang (2013) investigated the effects of the same variables on the general text quality of the learners.…”
Section: The Simultaneous Effect Of Resource-directing and Resource-dsupporting
confidence: 71%
See 1 more Smart Citation
“…The result of that study is in line with ours in terms of lexical complexity, but accuracy was not measured in their study. Similar to that study, Mohammadzadeh Mohammadabadi et al (2013) also did not find any interaction effect between planning time and here-and-now dimensions of task complexity. Additionally, Ong and Zhang (2013) investigated the effects of the same variables on the general text quality of the learners.…”
Section: The Simultaneous Effect Of Resource-directing and Resource-dsupporting
confidence: 71%
“…Moreover, Rahimpour and Safari (2011), studying the impact of pretask planning on EFL learners" descriptive texts, found the same results as ours with regard to accuracy; however, complexity was not significantly affected in their study. The findings of Mohammadzadeh Mohammadabadi et al (2013) are at odds with ours since the planning time provision was found to have positive impact on accuracy but not complexity. On the other hand, in contrast to our findings -and also to the predictions of task complexity models - Ong and Zhang (2010) detected that the writers performed the tasks more fluently and lexically-complex in the unplanned condition.…”
Section: Simin Sattarpour Et Alcontrasting
confidence: 56%
“…First and foremost, when language teachers are designing tasks for class activities, they should keep an eye to the variation in the level of difficulty so as to meet different needs of the students, and the task should also be interesting and realistic to students so that students could have free association for talking and strong motivation for interaction. Another problem in EFL context and more specifically in the Iranian EFL context, as noted by Mohammadzadeh, Dabaghi, and Tavakoli (2013), is that many teachers might avoid using a task-based approach on the account of the fact that it does not provide enough opportunity for language learners to focus on their speaking.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%
“…Using syntactic complexity (clauses per T-unit) and syntactic variety measures, they discovered that both pre-task and on-line planning do not influence the complexity of the written production. ISSN 1948-5425 2015 In the same vein, Mohammadzadeh et al (2013) conducted a study on thirty EFL learners (n=30) of lower-intermediate level. Task complexity was manipulated along resource-directing (+/-here-and-now) and resource-dispersing (+/-planning time) conditions.…”
Section: International Journal Of Linguisticsmentioning
confidence: 99%
“…A number of studies have found that planning condition may not affect the complexity of written production (e.g., Mehnert, 1998;Mohammadzadeh, Dabaghi & Tavakoli, 2013;Nariman-Jahan & Rahimpour, 2011;Piri, Barati & Ketabi, 2012;Rahimpour & Safarie, 2011). Rahimpour and Safarie (2011) conducted a study to explore the effects of pre-task planning (PTP) and on-line planning (OLP) on thirty seven (n=37) EFL learners.…”
Section: International Journal Of Linguisticsmentioning
confidence: 99%